2012
DOI: 10.1021/pr201128s
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin Heavy Chain Is the Host Factor Responsible for HCV-Induced Inhibition of apoB-100 Production and Is Required for Efficient Viral Infection

Abstract: Hepatic fat export occurs by apolipoprotein B-100-containing lipoprotein production, whereas impaired production leads to liver steatosis. Hepatitis C virus (HCV) infection is associated to dysregulation of apoB-100 secretion and steatosis; however, the molecular mechanism by which HCV affects the apoB-100 secretion is not understood. Here, combining quantitative proteomics and computational biology, we propose ferritin heavy chain (Fth) as being the cellular determinant of apoB-100 production inhibition. By m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…This could be rescued by FtH downregulation with specific siRNA. Interestingly, the reduction in FtH content was also associated with a less robust viral infection, thus indicating that FtH may be a host factor required for HCV infection (Mancone et al 2012). On the basis of the possible role of iron in the development of neurodegenerative processes, it is of particular interest a recent report showing that FtL can interact with Pen-2, a subunit of the multiprotein complex associated with the -secretase activity, involved in the processing of the amyloid precursor protein (Li et al 2013).The interaction has been found by the yeast two hybrid system and co-immunoprecipitation of the two proteins in cells overexpressing them.…”
Section: Mammalian Cytosolic Ferritin Not Only Ironmentioning
confidence: 99%
“…This could be rescued by FtH downregulation with specific siRNA. Interestingly, the reduction in FtH content was also associated with a less robust viral infection, thus indicating that FtH may be a host factor required for HCV infection (Mancone et al 2012). On the basis of the possible role of iron in the development of neurodegenerative processes, it is of particular interest a recent report showing that FtL can interact with Pen-2, a subunit of the multiprotein complex associated with the -secretase activity, involved in the processing of the amyloid precursor protein (Li et al 2013).The interaction has been found by the yeast two hybrid system and co-immunoprecipitation of the two proteins in cells overexpressing them.…”
Section: Mammalian Cytosolic Ferritin Not Only Ironmentioning
confidence: 99%
“…Indeed, the rate-limiting enzyme of VLDL production, microsomal triglyceride transfer protein (MTP), is transcriptionally repressed by HCV gene expression both in vitro [43], and in vivo [44], and associates with steatosis [44]. Recent studies suggest that the virus-induced dysregulation of apoB-100 secretion is mediated by increased ferritin heavy chain levels [45]. Indeed, an inverse correlation between ferritin and secreted apoB-100 concentrations is found both in JFH-1 HCVcc and HCV-infected patients, indicating a possible explanation for the onset of virus-induced liver steatosis [45].…”
Section: Lipids Apolipoproteins and Hcv Pathogenesismentioning
confidence: 99%
“…Recent studies suggest that the virus-induced dysregulation of apoB-100 secretion is mediated by increased ferritin heavy chain levels [45]. Indeed, an inverse correlation between ferritin and secreted apoB-100 concentrations is found both in JFH-1 HCVcc and HCV-infected patients, indicating a possible explanation for the onset of virus-induced liver steatosis [45]. Steatosis is not only caused by HCV, but is also linked to pathogenesis and enhanced disease progression.…”
Section: Lipids Apolipoproteins and Hcv Pathogenesismentioning
confidence: 99%
“…In particular, studies on HCV (hepatitis-C-virus) transgenic mice fed an excess-iron diet demonstrated that hepatic iron overload exacerbates the imbalance of lipid metabolism by both lipogenesis activation and reduced oxidation activity of fatty acids [1], [2]. Moreover, HCV-induced iron accumulation contributes to liver steatosis by the inhibition of β-lipoproteins mediated fat export, thus leading hypobetalipoproteinemia [3], [4]. In this study, male B6HCV-transgenic mice [5] expressing the HCV polyprotein were fed a low-iron diet or a control diet for thirty days.…”
Section: Experimental Designmentioning
confidence: 99%